The Wood Street Cake - Swinburne, Layinka (Petits Propos Culinaires, 2012)
An investigation into the Wood Street Cake which had associations with exiled royalty at the time of the  English Civil War. The paper looks at various historic recipes for this and other examples of what were known as Great Cakes, confections calling for large amounts of dried fruits (esp. currants) and other expensive ingredients.